2001
DOI: 10.1037/0022-3514.81.6.1014
|View full text |Cite
|
Sign up to set email alerts
|

The automated will: Nonconscious activation and pursuit of behavioral goals.

Abstract: It is proposed that goals can be activated outside of awareness and then operate nonconsciously to guide self-regulation effectively (J. A. Bargh, 1990). Five experiments are reported in which the goal either to perform well or to cooperate was activated, without the awareness of participants, through a priming manipulation. In Experiment 1 priming of the goal to perform well caused participants to perform comparatively better on an intellectual task. In Experiment 2 priming of the goal to cooperate caused par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
1,519
15
24

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,538 publications
(1,644 citation statements)
references
References 75 publications
65
1,519
15
24
Order By: Relevance
“…After completing the perceptual task, participants performed an anagram task to measure goal striving. Successful performance on anagram tasks is a common measure of goal pursuit in social psychological studies of achievement (e.g., Bargh et al, 2001; Elliott et al, 2007; Shah, 2003); performance tends to correlate highly with persistence but has the advantage of also tapping into how much effort participants expend, and how well they concentrate, two other markers of goal-driven behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After completing the perceptual task, participants performed an anagram task to measure goal striving. Successful performance on anagram tasks is a common measure of goal pursuit in social psychological studies of achievement (e.g., Bargh et al, 2001; Elliott et al, 2007; Shah, 2003); performance tends to correlate highly with persistence but has the advantage of also tapping into how much effort participants expend, and how well they concentrate, two other markers of goal-driven behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis that the observation of others attaining their goals might derail observers’ own goal pursuit is based on past research on goal completion. It is well established that goals are inhibited and cease to influence behaviors when individuals succeed at attaining those goals (Bargh, Gollwitzer, Lee-Chai, Barndollar & Troetschel, 2001; Förster et al, 2005; Marsh, Hicks, & Bink, 1998). For example, participants with a search goal (vs. no goal) showed heightened accessibility of search-related words before a search task, but showed reduced accessibility of those same words after they successfully completed the search task (Förster et al, 2005).…”
Section: Goal Satiationmentioning
confidence: 99%
“…At the moment, there are few data on these issues, but prior research has found that goal primes can alter responses outside of the laboratory (Fitzsimons & Bargh, 2003). Also, Bargh et al (2001) found that the effects of goal primes become stronger over time if the goal remains unsatiated. Taken together, these data suggest that goal primes may influence placebo expectations in producing the placebo effect in a nonlaboratory context and over a longer span of time.…”
Section: Studymentioning
confidence: 99%
“…Related to these more complex phenomena are the extensive demonstrations by Bargh and others how unconscious (automated, uncontrolled) processes guide and control overt and conscious action, e.g., Bargh (2001) and Uleman & Bargh(1989).…”
mentioning
confidence: 99%